The valorization of poppy seed cake for Pickering stabilization of functional ice creams - Nujamee Ngasakul; Michaela Freyová; Ali Kozlu; Diana Karina Baigts Allende; Iveta Klojdová (Future Foods)
This study aimed to valorize poppy seed cake by its incorporation into functional vegan ice creams based on coconut milk. Poppy seed cake's phytochemical composition (phenolics and flavonoids) was analyzed alongside its antioxidant activities (DPPH scavenging activity, FRAP assay, and metal chelating activity). Subsequently, Pickering emulsions stabilized with varying concentrations of poppy seed cake, and different hydrocolloids (carrageenan, Arabic gum) were prepared. Selected Pickering emulsion was then utilized to develop functional plant-based ice creams. Increasing the concentration of poppy seed cake resulted in increased particle size of Pickering emulsion 37.3 ± 1.5 μm to 51.1 ± 2.3 μm and a decrease in lightness (L*), consistent with the appearance of Pickering emulsion. Moreover, the enhanced hardness and viscosity of the emulsion were observed with higher concentrations of poppy seed cake, particularly when the hydrocolloid was incorporated, confirming the synergistic effects of hydrocolloids and poppy seed cake. For functional plant-based ice cream, all samples exhibited a typical shear-thinning behavior. Notably, coconut milk-based ice cream showed a significantly higher hardness, especially when carrageenan was added, with moderate viscosity. These findings highlight the potential of poppy seed cake as a valuable ingredient for future food development, improving the nutritional and functional properties of products.